Free vibration of layered cylindrical shells filled with fluid - Nurul Izyan, M. D. (Springer Netherlands, 2016)
The vibration of the layered cylindrical shells filled with a quiescent, incompressible, and inviscid fluid is analyzed. The governing equations of the cylindrical shells are derived by Love’s approximation. The solutions of the displacement functions are assumed in a separable form to obtain a system of coupled differential equations in terms of the displacement functions. The displacement functions are approximated by Bickley-type splines. A generalized eigenvalue problem is obtained and solved numerically for the frequency parameter and an associated eigenvector of the spline coefficients. Two layered shells with three different types of materials under clamped-clamped (C-C) and simply supported (S-S) boundary conditions are considered. The variations of the frequency parameter with respect to the relative layer thickness, the length-to-radius ratio, the length-to-thickness ratio, and the circumferential node number are analyzed.